Padronização e teste da técnica de imunofluorescência direta para o diagnóstico da cinomose canina - Gissandra Farias Braz (2009)
The objective of the present study was standardized and evaluated the Direct immunofluorescence assay (DIF) in the diagnosis of canine distemper. Genital mucous membrane, nasal and ocular smears from 40 dogs (32 with clinically suspected distemper symptoms and 8 with no clinical signs of distemper) was used. Thirty out of 32 dogs undersuspection of disease were positive (93.8%), and 8 out of 8 dogs with no clinical signs of distemper were negative by DIF assay. Our results demonstrated high agreement between clinical signs and DIF diagnosis (Kappa: 0.85), presenting a relative sensitivity and specificity of 93.8% and 100%, respectively. Positive results in DIF reach up to 87.5% in genital mucous, 67.7% in nasal, and 51.6% in conjunctival smears. The Cochran's Q statistics conclude that there is a statistically significant difference among the three specimens. The results agreement among animals presenting distemper clinical signs and specimens tested in DIF ranged from 50 to 87.5%, and animals with no signs of disease with the same test DIF was 100%. The highest agreement between symptoms and positive results in DIF were observed with genital impression samples (Kappa: 0.73) and in animals with systemic symptoms